Re-sperm collection with a short abstinence time: a strategy for successful cryopreservation in cryptozoospermia - Wen-Rui Zhao; Bo Liu; Xue-Feng Luo; Jin-Yan Xu; Chen Luo; Yuan Liu; Yang Xian; Fu-Ping Li (Journal of Men's Health)
Background: Recent studies suggest that short-term abstinence may improve semen parameters; however, its impact on cryptozoospermia remains underexplored. This study aimed to evaluate the impact of a 2-hour abstinence interval on sperm cryopreservation outcomes and assisted reproductive success in patients with cryptozoospermia. Methods: This retrospective study was conducted at a human sperm bank affiliated with a tertiary hospital from September 2023 to September 2024. A total of 78 patients diagnosed with cryptozoospermia or severe oligozoospermia undergoing fertility preservation were included. Each participant provided two semen samples via masturbation: the first after 2–7 days of abstinence, and the second following a 2-hour abstinence interval. The study compared sperm cryopreservation efficacy and assisted reproductive outcomes between these two collection protocols. Results: Comparative analysis revealed a significant reduction in semen volume with short-term abstinence (p < 0.001). Notably, in cryptozoospermic patients, the second sample showed a significantly higher motile sperm concentration (p = 0.003), increasing cryopreservation success rates from 53.19% (25/47) to 63.83% (30/47). However, no significant difference was observed in post-thaw sperm survival rates between the first and second samples (45.59% ± 21.16% vs. 40.83% ± 19.82%, p = 0.626). Preliminary clinical data from 7 patients utilizing cryopreserved sperm revealed 4 clinical pregnancies, including 2 live births. Conclusions: These findings indicate that short-interval sperm collection enhances cryopreservation feasibility for cryptozoospermic patients without compromising post-thaw viability, potentially reducing reliance on invasive testicular sperm extraction. While larger prospective studies are needed to confirm these reproductive outcome benefits, this dual-collection protocol offers a cost-effective strategy to optimize sperm availability for intracytoplasmic sperm injection cycles in cases of severe male factor infertility. These results highlight the clinical value of tailored abstinence protocols in fertility preservation programs.